The everglades handbook : - Lodge, Thomas E. (CRC Press, 2004)
The second edition of a bestseller, The Everglades Handbook: Understanding the Ecosystem continues to provide a wealth of information on the entire ecosystem of the Everglades. With an emphasis on natural history, the text is unified around themes of biogeography and ecosystem functions of the plant and animal communities. It presents current and historical geology, discussions of human impacts, ecosystem degradation, planned restoration, and covers the socioeconomic aspects of the Everglades ecosystem